2019
DOI: 10.1186/s12929-019-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein (HBx) enhances centrosomal P4.1-associated protein (CPAP) expression to promote hepatocarcinogenesis

Abstract: Background Our previous report suggested that centrosomal P4.1-associated protein (CPAP) is required for Hepatitis B virus (HBV) encoded non-structure protein X (HBx)-mediated nuclear factor kappa light chain enhancer of activated B cells (NF-κB) activation. CPAP is overexpressed in HBV-associated hepatocellular carcinoma (HCC); however, the interaction between CPAP and HBx in HBV-HCC remains unclear. Methods The mRNA expression of CPAP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Recent studies have found that the m 6 A modification, when the related enzyme is abnormal, plays various roles in a series of human diseases such as neurological disorders, cancer, and embryonic developmental retardation (Wu et al, 2019). Both coding RNAs and some non-coding RNAs, such as lncRNA, microRNA, tRNA, and rRNA and RNA splice body, were regulated by an m 6 A modification before and after transcription (Yen et al, 2019). N6-methyladenosine modification is closely related to the metabolic processes of RNAs, for example, RNA processing, RNA transfer from the nucleus to the cytoplasm, RNA translation, RNA decay, and the biogenesis of RNA (Liang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the m 6 A modification, when the related enzyme is abnormal, plays various roles in a series of human diseases such as neurological disorders, cancer, and embryonic developmental retardation (Wu et al, 2019). Both coding RNAs and some non-coding RNAs, such as lncRNA, microRNA, tRNA, and rRNA and RNA splice body, were regulated by an m 6 A modification before and after transcription (Yen et al, 2019). N6-methyladenosine modification is closely related to the metabolic processes of RNAs, for example, RNA processing, RNA transfer from the nucleus to the cytoplasm, RNA translation, RNA decay, and the biogenesis of RNA (Liang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CPAP was reported to be an essential factor for TNF-α-mediated NF-κB and IL-6-mediated STAT3 activation in HCC [ 29 31 ]. Upon HBV infection, the viral oncoprotein HBx transcriptionally increases the expression of CPAP to enhance HCC development [ 30 ]. To evaluate the effects of CPAP in hepatocarcinogenesis, we assessed the physiological roles of overexpressed CPAP in hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that HBV-induced chronic liver inflammation is considered a major causative factor of hepatocarcinogenesis [ 4 , 34 ]. CPAP increases HBx protein stability in an NF-κB-dependent manner, and facilitates HCC growth and progression [ 30 ]. To further investigate the ability of overexpressed CPAP in inflammation-induced hepatocarcinogenesis, we generated CH Tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…Promote cancer cell proliferation and poorer survival (Bai et al 2019) Up-regulation in gastric cancer cells Promote cell proliferation in cancers by regulating mitotic nuclear division (Song et al 2018) MCPH5/ASPM Overexpression in bladder cancer cells Aggressiveness and poor outcome (Xu et al 2019) Up-regulation in pancreatic ductal adenocarcinoma More aggressiveness and treatment-resistant malignancy (Wang et al 2013a, b) Increased expression in prostate cancer cells Promote tumor cell progression (Pai et al 2019) Overexpression in glioblastoma cells Tumor cell proliferation (Horvath et al 2006) Overexpressed in hepatocellular carcinoma cells Vascular invasion, early recurrence, and poor prognosis (Lin et al 2008) MCPH6/CENPE Overexpressed in HBV-associated hepatocellular carcinoma Promote cancer malignancies (Yen et al 2019) MCPH7/STIL Upregulated in gastric cancer Promote progression and poor overall survival (Wang et al 2019) Upregulated in lung cancer Enhance metastatic spread (Erez et al 2004) Upregulated in colon carcinoma, prostate adenocarcinoma, ovarian cancers Poor prognosis (Erez et al 2004;Wu et al 2019;Rabinowicz et al 2017) Increased expression in pancreatic carcinoma, glioblastoma, kidney carcinoma and cervix adenocarcinoma…”
Section: Mcph4/knl1 Increased Expression Level In Colorectal Cancer Cmentioning
confidence: 99%